2014
DOI: 10.1074/jbc.m114.591578
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Heat Shock Element Sequences Drive Cooperative Human Heat Shock Factor 1 DNA Binding and Selectivity

Abstract: Background: Heat shock factor 1 is a stress-responsive transcription factor that targets diverse genomic loci. Results: Extended and cooperatively oriented genomic binding sequences dictate HSF1 DNA binding specificity. Conclusion: Cooperativity in HSF1 DNA binding strongly influences the constellation of bound target genes. Significance: Differential HSF1 target gene selectivity may underlie the diverse functions for HSF1 in protein misfolding disease and cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…Using fluorescence polarization and thermal denaturation profiling combined with quantitative chromatin immunoprecipitation assays, Jaeger et al . have demonstrated a role for specific orientations of extended HSE sequences in driving preferential HSF1 DNA binding to its target loci.…”
Section: Hsf1mentioning
confidence: 99%
“…Using fluorescence polarization and thermal denaturation profiling combined with quantitative chromatin immunoprecipitation assays, Jaeger et al . have demonstrated a role for specific orientations of extended HSE sequences in driving preferential HSF1 DNA binding to its target loci.…”
Section: Hsf1mentioning
confidence: 99%
“…The cellular response to hyperthermia is mediated by trimerization of the temperature-sensitive transcription factor Heat Shock Factor 1 (HSF1) and its subsequent binding to DNA motifs termed Heat Shock Elements (HSEs). HSEs are comprised of multiple inverted repeats of the consensus sequence 5'-nGAAn-3' 28,29 and are arrayed upstream of HSPs thereby enabling their upregulation following thermal stress 30 . The response of endogenous HSP genes is selective, but not specific, for heat as their promoters contain additional regulatory elements (e.g., hypoxia response elements 31 , metal-responsive elements 32 ) that mediate transcription following exposure to a diverse set of cues including hypoxia 33 , heavy metals 34 , and mechanical force 35 .…”
Section: Engineering Thermal-specific Gene Switchesmentioning
confidence: 99%
“…We did not detect CpG methylation in a region driving basal transcriptional activity. However, region-1, which contains some sequences similar to heat shock transcription factor 1 (HSF1) binding motifs ( Jaeger et al, 2014;Trinklein et al, 2004), was found to be methylated in all cell lines (Fig. 5A), suggesting that methylation of this region could have some regulatory effects.…”
Section: Cpg Methylation In the 5¢-flanking Region Of Hlj1mentioning
confidence: 99%
“…4). According to our combined bisulfite restriction analysis (COBRA) results, the 5¢-flanking region having sequences similar to HSF1 binding motifs (heat shock elements [HSEs]) was found to be methylated in all breast cell lines ( Jaeger et al, 2014;Trinklein et al, 2004) (Fig. 5A).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation